Mesenteric Panniculitis - Cecilio Azar; Mohamad Ali Ibrahim; Zakaria El Kouzi; Ali El Mokahal; Nadine Omran; Nadim Muallem; Ala I. Sharara (Inflammatory Intestinal Diseases, 2024)
Background: Mesenteric panniculitis (MP) is an uncommon non-neoplastic idiopathic inflammation of adipose tissue, mainly affecting the mesentery of the small intestine, with its etiology remaining largely speculative. The difference in prevalence of MP among females and males varies across multiple studies. In most cases, MP is asymptomatic; however, patients can present with nonspecific abdominal symptoms or can mimic underlying gastrointestinal and abdominal diseases. The diagnosis is suggested by computed tomography and is usually confirmed by surgical biopsies if necessary. Treatment is generally supportive and based on a few selected drugs, namely, nonsteroidal anti-inflammatory drugs or corticosteroids. Surgery is reserved when the diagnosis is unclear, when malignancy is suspected or in the case of severe presentation such as mass effect, bowel obstruction, or ischemic changes. Summary: MP is a rare inflammatory condition of the mesentery often asymptomatic but can cause nonspecific abdominal symptoms. Diagnosis relies on computed tomography imaging, with treatment mainly supportive, utilizing medications like nonsteroidal anti-inflammatory drugs or corticosteroids, while surgery is reserved for severe cases or diagnostic uncertainty. Key Messages: MP causes abdominal pain, and it is mainly diagnosed with CT scan.